5-Carboxy-8-hydroxyquinoline is a broad spectrum 2-oxoglutarate oxygenase inhibitor which causes iron translocation - Hopkinson, R; Tumber, A; Yapp, C; Chowdhury, R; Aik, W; Che, K; Li, X; Kristensen, J; King, O; Chan, M; Yeoh, K; Choi, H; et al. (2013)
2-Oxoglutarate and iron dependent oxygenases are therapeutic targets for human diseases. Using a representative 2OG oxygenase panel, we compare the inhibitory activities of 5-carboxy-8-hydroxyquinoline (IOX1) and 4-carboxy-8-hydroxyquinoline (4C8HQ) with that of two other commonly used 2OG oxygenase inhibitors, N-oxalylglycine (NOG) and 2,4-pyridinedicarboxylic acid (2,4-PDCA). The results reveal that IOX1 has a broad spectrum of activity, as demonstrated by the inhibition of transcription factor hydroxylases, representatives of all 2OG dependent histone demethylase subfamilies, nucleic acid demethylases and γ-butyrobetaine hydroxylase. Cellular assays show that, unlike NOG and 2,4-PDCA, IOX1 is active against both cytosolic and nuclear 2OG oxygenases without ester derivatisation. Unexpectedly, crystallographic studies on these oxygenases demonstrate that IOX1, but not 4C8HQ, can cause translocation of the active site metal, revealing a rare example of protein ligand-induced metal movement. © 2013 The Royal Society of Chemistry.